Impact of clustering in AODV routing protocol for wireless body area network in remote health monitoring system - Wan Aida Nadia Wan Abdullah; Naimah Yaakob; R. Badlishah Ahmad; Mohamed Elshaikh Elobaid; Siti Asilah Yah (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Proper selection of routing protocol in transmitting and receiving medical data in Wireless Body Area Network (WBAN) is one of the approaches that would help in ensuring high network performances.  However, a continuous monitoring of health status through sensing of various vital body signals by multiple biosensors could produce a bulk of medical data and lead to the increase of network traffic. Occurrence of high traffic could result to network’s congestion which have high tendency to loss some of important (critical) data and cause longer delay that would lead to false diagnosis of diseases. In order to analyze and validate this issue, Ad-Hoc On Demand Distance Vector (AODV) which is known as reactive routing protocol is evaluated in WBAN scenario through varying number of nodes and clusters. The presence of clustering helps in reducing the burden of the sink nodes in handling high traffics. The network’s performances of this protocol are measured in terms of end to end delay, percentage packet loss, throughput and energy consumption using Network Simulator (NS-2). Based on the experimental results, the presence of cluster helps in improving network performances by achieving reduction in delay, packet loss and energy consumption. However, low throughput is achieved as number of clusters are increase due to low duty cycle of the nodes.